Synergic effect of salinity and zinc stress on growth and photosynthetic responses of the cordgrass, Spartina densiflora - Redondo-Gómez, Susana (Oxford University Press, 2011)
Spartina densiflora is a C(4) halophytic species that has proved to have a high invasive potential which derives from its physiological plasticity to environmental factors, such as salinity. It is found in coastal marshes of south-west Spain, growing over sediments with between 1 mmol l(−1) and 70 mmol l(−1) zinc. A glasshouse experiment was designed to investigate the synergic effect of zinc from 0 mmol l(−1) to 60 mmol l(−1) at 0, 1, and 3% NaCl on the growth and the photosynthetic apparatus of S. densiflora by measuring chlorophyll fluorescence parameters and gas exchange, and its recovery after removing zinc. Antioxidant enzyme activities and total zinc, sodium, calcium, iron, magnesium, manganese, phosphorus, potassium, and nitrogen concentrations were also determined. Spartina densiflora showed the highest growth at 1 mmol l(−1) zinc and 1% NaCl after 90 d of treatment; this enhanced growth was supported by the measurements of net photosynthetic rate (A). Furthermore, there was a stimulatory effect of salinity on accumulation of zinc in tillers of this species. Zinc concentrations >1 mmol l(−1) reduced growth of S. densiflora, regardless of salinity treatments. This declining growth may be attributed to a decrease in A caused by diffusional limitation of photosynthesis, owing to the modification of the potassium/calcium ratio. Also, zinc and salinity had a marked overall effect on the photochemical (photosystem II) apparatus, partially mediated by the accumulation of H(2)O(2) and subsequent oxidative damage. However, salinity favoured the recovery of the photosynthetic apparatus to the toxic action of zinc, and enhanced the nutrient uptake.